TVET Approaches: A Diagnosis through the Lens of Human Capital, Right Based and Capability Approach - Thapa, Binayak Krishna; Singh, Aishwarya Rani (Journal of Training and Development, 2019)
The key approaches utilised for the understanding and implementation of a Technical and Vocational Education and Training (TVET) are primarily human capital and human rights approaches. While human capital approach advocates enhanced skills for the productivity, human rights approach systematically demands distributed enhancement of skills through short- or long-term trainings for all. The former approach connotes economic growth through better employment and income opportunity, whereas the latter situates itself for distributive opportunity, social inclusion and social justice. Both approaches target increasing employment and enhancing chances for better livelihood and well-being. These two approaches, however, are not the ultimate and only approaches for understanding the technical and vocational education and training. The major limitations of these approaches are that they conceptualize employment, income, better opportunity and even distribution to be ends or goals, while in this paper, the authors argue that the mentioned concepts are just means to a general end that is human development. Given this context, this paper offers an alternative lens to look at technical and vocational education and training. This alternative lens is arguably capability approach. The capability lens potentially explains how skill enhancement improves the ‘being’ and ‘doing’ of a person who engages in taking training and how the trained person can implement the learned skills to improve his/her well-being. In this regard, this approach helps understand how TVET can directly be linked with human development. This paper finally argues that TVET is also a tool for human development, albeit it is primarily, still concerned with productivity, employment and better incomes.